Dear Mr. Henshaw - Cleary, Beverly; Zelinsky, Paul O. (New York HarperTrophy, 2000)
In his letters to his favorite author, ten-year-old Leigh reveals his problems in coping with his parents' divorce, being the new boy in school, and generally finding his own place in the world.
Keywords: Divorce -- Juvenile fiction; Parent and child -- Juvenile fiction; Schools -- Juvenile fiction; Letters -- Juvenile fiction; Divorce -- Fiction; Parent and child -- Fiction; Schools -- Fiction; Letters -- Fiction